Simultaneous determination of ionic polymers and heavy metal ions concentrations in aqueous solution after their adsorptive removal using eco-friendly activated biocarbons - Groszek, Marlena; Wiśniewska, Małgorzata; Nowicki, Piotr (Frontiers in Chemistry, 2025)
Growing contamination of aquatic systems by industrial and domestic pollutants necessitates the development of efficient and sustainable wastewater treatment technologies. Activated biocarbons derived from renewable biomass sources have proven to be promising materials for this purpose thanks to their large specific surface area, well-developed porosity, high content of surface groups and cost-effectiveness. This paper describes the preparation, physicochemical characterization and practical application of carbonaceous adsorbents derived from the nettle and mint herbs residues using an environmentally friendly method–single-stage (direct) physical activation with carbon dioxide. The obtained activated biocarbons were fully characterized in terms of their texture, surface properties, and chemical composition, and then used to remove ionic polymers (poly(acrylic acid) and polyethyleneimine) as well as Cd(II) and As(V) ions from aqueous solutions. The influence of the above-mentioned substances on their mutual adsorption was investigated. The obtained eco-friendly carbonaceous materials are characterized by moderately developed surface area (368–666 m2/g) and high content of the surface functional groups (2.19–4.89 mmol/g). The maximum adsorbed amounts of ionic polymers reached the level of about 80 mg/g, while those of heavy metal ions varied in the range of 4–19 mg/g. Competitive adsorption between the polymer chains and heavy metal ions was confirmed. In the binary system containing both types of macromolecules, an increase in the adsorbed amounts of poly(acrylic acid) and polyethyleneimine was observed. In turn, the simultaneous presence of ionic polymers and heavy metal ions leads to a reduction in the adsorbed quantities of all adsorbates. The analysis of adsorption-desorption, surface, and electrokinetic data allowed the identification of the most probable mechanisms of separation of ionic polymers and heavy metal ions from the aqueous phase using eco-friendly carbonaceous adsorbents.